Investigation Of Antimicrobial And Antioxidant Activity Of The Methanolic Extract Of The Leaves Of Voacanga Africana Stapf. (Apocynaceae) And Psydrax Subcordata (Dc.) Bridson (Rubiaceae) - Olaofe Oyawaluja, Bamisaye; Aribiba Williams, Josephine; A. B. Coker, Herbert (The Nigerian Journal of Pharmacy, 2019)
Background The importance of medicinal plants in traditional and modern health care practices and in providing clues to new areas of research is now well recognised. Bacterial resistance has been increasingly reported worldwide and is one of the major causes of failure in the treatment of infectious diseases. Plant derived antioxidant could be useful as food additives to prevent food deterioration and also to impart human health and prevent oxidative stress associated diseases. Naturalbased products, including plant secondary metabolites (phytochemicals), can be exploited to ameliorate the problem of microbial resistance and oxidative stress. The choice of plants (Voacanga africana and Psydrax subcordata) for this study was based on folkloric use and literature search to authenticate the traditi on claims. Methods The leaves methanolic extract of Voacanga africana and Psydrax subcordata were investigated for antimicrobial and antioxidant activity. The antimicrobial activities were also evaluated using the agar well diffusion method while the antioxidant activities of the plants were evaluated using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, nitric oxide scavenging assay, lipid peroxidati on scavenging assay, total antioxidant capacity assay, total phenolic content, total flavonoid content and ferric reducing power assay. Results The extracts of Voacanga africana and Psydrax subcordata significantly inhibited DPPH radical with an IC50 value of 69.2±11.6µg/ml and 106.9±5.3µg/ml respectively), inhibited lipid peroxidation (IC50 value of 65.7±13.5µg/ml and 75.4±11.6 µg/ml respectively) and also inhibited the accumulation of nitrite in vitro (IC50 value of 75.1±11.7µg/ml and 80.1±12.9µg/ml respectively). The plant extracts yielded 47.8±0.07 and 65.2±0.04mg Gallic acid equivalent/100g phenolic content respecti vely, 2.8±0.05mg and 28.2±0.05mg quercetin equivalents/100g flavonoid content respectively, total antioxidant capacity of 160.6±0.05 and 110.7±0.05mg ascorbic equivalent/100g and reducing power of 0.2±0.07 and 0.2±0.05µg/ml, respecti vely. The anti microbial assay showed that Voacanga africana has activity against gram positive and gram negati ve bacteria organisms, which include Staphylococcus aureus (34.0±1.2), Bacillus subtilis (37.5±0.0) and Pseudomonas aeruginosa (35.5±0.9) at 50µg/ml. Psydrax subcordata was only active against Staphylococcus aureus (20.8±0.5). However, no antifungal activity was observed for both plants. Conclusion Voacanga africana and Psydrax subcordata possess anti oxidant and anti microbial acti viti es and these results therefore provide evidence to support their traditional uses. The observed antioxidant potentials and phenolic content of the extract suggest that the methanolic leaves extract of Voacanga africana and Psydrax subcordata is a potential source of natural antioxidants.